PERAN RISIKO PEMBIAYAAN DALAM MEMODERASI PENGARUH EFISIENSI OPERASIONAL DAN PERMODALAN TERHADAP PROFITABILITAS BPRS DI JAWA TIMUR - Fena Nurmala; Firdha Aksari Anindyntha (Journal of Financial Economics & Investment, 2026)
Sharia Rural Banks have a strategic role in financing the micro sector, but profitability as measured by Return on Assets (ROA) shows fluctuations and tends to decline during the 2020-2024 periods. This study aims to analyze the effect of operational efficiency (BOPO) and capital structure (CAR) on profitability (ROA) with financing risk (NPF) as a moderating variable at BPRS in East Java for the 2020-2024 periods. This study uses panel data, namely a combination of time series data for the 2020-2024 period and a cross-section of 24 BPRS resulting in 120 observations, with the analysis technique Moderated Analysis Regression using the Common Effect Model. The results show that operational efficiency, capital structure, and financing risk have a significant negative effect on bank profitability. The moderation test shows that NPF is unable to moderate the effect of BOPO and CAR on ROA. These findings indicate that operational efficiency and capitalization have a direct impact on profitability, regardless of the level of financing risk. This research contributes to the development of Islamic banking literature as well as managerial implications for BPRS in increasing efficiency, optimizing capital, and sustainable management of financing quality.